CHEMICAL AND PHYSICAL FRACTIONATION OF THE ORGANIC MATTER OF A CAMBISOL AFTER 21 YEARS UNDER DIFFERENT PREPARATIONS - Andrade, Andreia Patricia; Rauber, Luiz Paulo; Bagio, BÃ¡rbara; Wolschick, Neuro Hilton; Mafra, Ãlvaro Luiz; Bertol, Ildegardis (REVISTA DE AGRICULTURA, 2020)
Soil organic carbon is used as an indicator of soil quality. The objective of this study was to evaluate chemical and physical fractions of the organic carbon in a Humic Cambisol under different tillage for 21 years. The treatments were conventional tillage (CT) and no-tillage (NT). As reference area, a native grassland (NF), next to the experiment, was evaluated. Samples were collected at three depths. Total (TOC) and particulate organic carbon (POC) concentrations and stocks and humic substances (HS) were evaluated.Â  The TOC and POC were higher in the NF than in the crop systems. NT has more carbon than CT in the humin and humic acid fractions in the surface soil. Physical fractions of organic carbon are similar between the management systems. NT has a greater organic carbon stock than CT 15 years after its development and shows greater potential for carbon conservation in the surface soil. Thus, long-term experiments are important to monitor soil behavior under different management conditions.